Influence of insecticide resistance on the biting and resting preferences of malaria vectors in the Gambia - Hamid-Adiamoh, Majidah; Nwakanma, Davis; Assogba, Benoit Sessinou (My University, 2021)
Background The scale-up of indoor residual spraying and long-lasting insecticidal nets, together with other interventions have considerably reduced the malaria burden in The Gambia. This study examined the biting and resting preferences of the local insecticide-resistant vector populations few years following scale-up of anti-vector interventions Method Indoor and outdoor-resting Anopheles gambiae mosquitoes were collected between July and October 2019 from ten villages in five regions in The Gambia using pyrethrum spray collection (indoor) and prokopack aspirator from pit traps (outdoor). Polymerase chain reaction assays were performed to identify molecular species, insecticide resistance mutations, Plasmodium infection rate and host blood meal. Results A total of 844 mosquitoes were collected both indoors (421, 49.9%) and outdoors (423, 50.1%). Four main vector species were identified, including An. arabiensis (indoor: 15%, outdoor: 26%); An. coluzzii (indoor: 19%, outdoor: 6%), An. gambiae s.s. (indoor: 11%, outdoor: 16%), An. melas (indoor: 2%, outdoor: 0.1%) and hybrids of An. coluzzii-An. gambiae s.s (indoors: 3%, outdoors: 2%). A significant preference for outdoor resting was observed in An. arabiensis (Pearson X2 = 22.7, df = 4, P<0.001). Prevalence of the voltage-gated sodium channel (Vgsc)-1014S was significantly higher in the indoor-resting (allele freq. = 0.96, 95%CI: 0.78– 1, P = 0.03) than outdoor-resting (allele freq. = 0.82, 95%CI: 0.76–0.87) An. arabiensis population. For An. coluzzii, the prevalence of most mutation markers was higher in the outdoor (allele freq. = 0.92, 95%CI: 0.81–0.98) than indoor-resting (allele freq. = 0.78, 95%CI: 0.56– 0.86) mosquitoes. However, in An. gambiae s.s., the prevalence of Vgsc-1014F, Vgsc1575Y and GSTe2-114T was high (allele freq. = 0.96–1), but did not vary by resting location. The overall sporozoite positivity rate was 1.3% (95% CI: 0.5–2%) in mosquito populations. Indoor-resting An. coluzzii had mainly fed on human blood while indoor-resting An. arabiensis fed on animal blood. Conclusion In this study, high levels of resistance mutations were observed that could be influencing the mosquito populations to rest indoors or outdoors. The prevalent animal-biting behaviour demonstrated in the mosquito populations suggest that larval source management could be an intervention to complement vector control in this setting.
Keywords: Mamadou Ousmane Ndiath; Umberto D’Alessandro; Yaw A. Afrane; Alfred Amambua-Ngwa; WACCBIP; malaria; insecticide-resistant vector; Plasmodium